A case of intestinal malrotation apparent after laparoscopically total proctocolectomy followed by ileal‐pouch‐anal anastomosis for ulcerative colitis. Issue 1 (11th August 2022) - Ichikawa, Hidetaka; Ohnuma, Shinobu; Imoto, Hirofumi; Kageyama, Sakiko; Kobayashi, Minoru; Kajiwara, Taiki; Karasawa, Hideaki; Kohyama, Atsushi; Watanabe, Kazuhiro; Tanaka, Naoki; Kamei, Takashi; Unno, Michiaki
Abstract: Intestinal malrotation (IM) is an abnormality due to a failure of the normal midgut rotation and fixation. We report a case of 46‐year‐old man with ulcerative colitis whose IM was apparent after laparoscopically total proctocolectomy (TPC) followed by ileal‐pouch‐anal anastomosis (IPAA) and ileostomy. There was no abnormal anatomy except for mobile cecum/ascending colon during the initial operation. Intestinal obstruction occurred after ileostomy closure. The computed tomography scan showed the duodeno‐jejunal transition was located in right abdomen, the superior mesenteric vein was located left of the superior mesenteric artery (SMA) and the obstruction point was the distal ileum near the pouch. We performed an ileo‐ileo bypass across the ventral side of the SMA to relieve the intestinal obstruction. The patient would have incomplete IM preoperatively, which became apparent by TPC. In case of TPC for mobile colon, anatomy of small intestine should be checked before IPAA.